Lubrication and Drag Reduction for Polymer-Coated Interfaces - Qiang Yang; Xiang Ben; Jingkai Lin; Yuhao Zhang; Li Xiang; Zhiyong Wei; Yajing Kan (Lubricants)
Lubrication is a well-established strategy for reducing interfacial frictional energy dissipation and preventing surface wear. Various lubricants have been developed, including mineral oil materials, vegetable oil materials, polymer-based materials, and solid lubrication materials. Among these, polymer-based lubrication materials have gained significant interest due to their versatility, leading to the development of tailored strategies to meet diverse application demands. In load-bearing scenarios, polymer-based materials enhance interfacial hydration, exhibiting exceptional frictional properties, including extremely low friction coefficients, high load-bearing capacity, and superior wear resistance. In contrast, in non-load-bearing scenarios, polymer-based coatings improve interfacial hydrophobicity, promoting boundary slip and reducing frictional resistance at the solid–liquid interface (SLI), making them an important strategy for drag reduction. Despite substantial advancements in polymer-based lubrication and drag reduction (PBLDR), the underlying microscopic mechanisms remain incompletely understood. Therefore, this review aims to provide a comprehensive analysis of the fundamental principles governing PBLDR. The main topics covered will include the following: (1) the fundamentals of the surface forces and hydrodynamic force, (2) the mechanisms underlying hydration lubrication, (3) joint lubrication and polymer brush lubrication, (4) the friction tuning and interfacial drag reduction via polymer coating design, and (5) the potential and limitations of polymer-based materials. By summarizing recent advancements in PBLDR, this work will provide valuable contributions to future research and applications in related fields.